One-Year MRI Outcomes of Osteochondral Allograft Transplantation of the Knee for Large Chondral Defects: Comparison of Elliptical, Stacked, and Single Allografts. Issue 7 (31st July 2020) - Wang, Dean; Ode, Gabriella; Elbuluk, Ameer; Burge, Alissa; Jones, Kristofer; Williams, Riley; Coxe, Francesca
Objectives: Osteochondral allograft transplantation (OCA) is a proven cartilage restoration procedure for patients with large chondral defects. However, elongated condylar lesions pose a challenge for dowel OCA in restoring articular surface congruity. Recently, instrumentation to harvest a single, elliptical allograft has been developed for treating ovoid lesions without requiring an adjacent-plug (stacked or snowman) technique. The purpose of this study was to compare 1-year MRI outcomes of patients treated with elliptical, stacked, or single OCA using the Osteochondral Allograft MRI Scoring System (OCAMRISS) and percent osseous integration. Methods: A retrospective review on patients treated from 2000 to 2018 with OCA for condylar defects of the knee was conducted. Inclusion criteria included those followed prospectively with a MRI at ˜1 year after surgery. OCAMRISS and osseous integration scores (0-25%; 26-50%; 51-75%; 76%-100%) were graded by a musculoskeletal radiologist blinded to the outcomes. Comparisons of demographics and MRI scores were performed with the ANOVA. Results: A total of 57 knees (mean age, 35.8 years; 70% male) met the inclusion criteria and were treated with either elliptical (n=19), stacked (n=19), or single (n=19) OCA. Mean time to post-operative MRI was 10.7, 11.1, and 12.4 months, respectively (p=0.17). There were no significant differences in demographics or number of prior ipsilateral knee surgeries among groups. Defect characteristics were significantly different between groups, where single plugs treated a higher percentage of LFC defects (58%) compared to elliptical and stacked (26%, each) (p=0.02). Total chondral defect area was greatest in the stacked group (5.4 ± 1.3) compared to elliptical (4.6 ± 1.2) and single (4.6 ± 1.4) (p=0.12). Bone, cartilage, ancillary, and total OCAMRISS scores were not significantly different between groups. A trend towards a higher percentage of osseous integration (single>stacked>elliptical) was noted which correlated with less transplanted allograft bone, however, these differences were not significant (p=0.15). Conclusion: One-year OCAMRISS and osseous integration scores did not differ among patients treated with elliptical, stacked, or single OCA. Further investigation is needed to explore potential differences in clinical outcomes and long-term osseous integration between elliptical and stacked OCA for the treatment of elongated condylar defects of the knee. Table 1. Patient Demographics, Intraoperative Data, and OCAMRISS Scores at 1-year Postoperative MRI Elliptical (n = 19) Stacked (n = 19) Single (n = 19) P Value Patient Characteristics Age, y 37.0 ± 13.9 37.5 ± 11.1 33.1 ± 11.8 0.48 Sex (male/female), n 14/5 13/6 13/6 0.92 Body mass index, kg/m 2 25.7 ± 2.8 26.5 ± 5.0 25.9 ± 3.2 0.78 No. of prior ipsilateral knee surgeries 1.1 ± 1.4 1.9 ± 2.4 1.4 ± 0.8 0.29 MRI follow-up, mo 10.7 ± 3.9 11.1 ± 1.9 12.4 ± 2.2 0.17 Lesion Characteristics OCA location, n (%) 0.02 Medial femoral condyle 14 (74) 14 (74) 8 (42) Lateral femoral condyle 5 (26) 5 (26) 11 (58) Total chondral defect area, cm 2 4.6 ± 1.2 5.4 ± 1.3 4.6 ± 1.4 0.12 OCAMRISS Score Cartilage features 3.5 ± 1.5 2.9 ± 1.5 3.4 ± 2.1 0.48 Bone features 3.0 ± 0.7 2.7 ± 0.7 2.8 ± 0.6 0.30 Ancillary features 3.0 ± 1.1 2.9 ± 1.0 2.6 ± 1.1 0.46 Total 9.5 ± 2.1 8.4 ± 2.5 8.8 ± 3.1 0.45 Osseous Integration Score 2.1 ± 1.1 1.7 ± 0.90 1.5 ± 0.60 0.15